2016
DOI: 10.1016/j.bbalip.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the S1P3 receptor in metastatic breast cancer cells increases migration and invasion by induction of PGE2 and EP2/EP4 activation

Abstract: Breast cancer is one of the most common and devastating malignancies among women worldwide. Recent evidence suggests that malignant progression is also driven by processes involving the sphingolipid molecule sphingosine 1-phosphate (S1P) and its binding to cognate receptor subtypes on the cell surface. To investigate the effect of this interaction on the metastatic phenotype, we used the breast cancer cell line MDA-MB-231 and the sublines 4175 and 1833 derived from lung and bone metastases in nude mice, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…The migratory capacity of cells was measured in an adapted Boyden chamber assay. Both metastatic cell lines showed enhanced migration compared to the parental cells ( Figure 2), which confirms previous findings in this metastases model [26]. As expected, in the presence of the CerK inhibitor NVP-231 [27], migration of the two sublines dose-dependently decreased (Figure 2), reaching maximal inhibition of 30% at 1 μM in 4175 cells and of 70% at 1 μM in 1833 cells.…”
Section: Int J Mol Sci 2019 20 X For Peer Review 3 Of 13supporting
confidence: 89%
See 3 more Smart Citations
“…The migratory capacity of cells was measured in an adapted Boyden chamber assay. Both metastatic cell lines showed enhanced migration compared to the parental cells ( Figure 2), which confirms previous findings in this metastases model [26]. As expected, in the presence of the CerK inhibitor NVP-231 [27], migration of the two sublines dose-dependently decreased (Figure 2), reaching maximal inhibition of 30% at 1 μM in 4175 cells and of 70% at 1 μM in 1833 cells.…”
Section: Int J Mol Sci 2019 20 X For Peer Review 3 Of 13supporting
confidence: 89%
“…As expected, in the presence of the CerK inhibitor NVP-231 [27], migration of the two sublines dose-dependently decreased (Figure 2 Another feature of metastatic cells is invasiveness [28,29]. We previously reported that the 4175 and the 1833 sublines also have an increased capacity of invasion, as detected in a Matrigel assay [26]. Here, we found that this process was also mitigated by the CerK inhibitor NVP-231 ( Figure 3).…”
Section: Int J Mol Sci 2019 20 X For Peer Review 3 Of 13supporting
confidence: 80%
See 2 more Smart Citations
“…Inflammation is emerging as a new hallmark of cancer metastasis and invasion and cyclooxygenases (COXs) and lipoxygenase (LOX) play major roles in arachidonic acid-related inflammatory cascades [23,24]. Previous studies show that COX-2 as a rate-limiting enzyme involved in the formation of PGE2 from arachidonic acid, and is over-expressed in the colorectal cancer tumor tissues.…”
Section: Discussionmentioning
confidence: 99%